The influence of Destination Branding and Authenticity on Tourism: Analysing the tourist experience - Case Study of Lisbon - Oliveira, Ana Filipa Figueiredo de (My University, 2019)
Destination Branding: a concept that has guided the tourism industry since day one. It strengthens the position of the product in the tourism market and helps it to remain competitive. It has also been an efficient tool to give an image to places and transmit this image to the final consumer. But how much “realness” does this image transmit? Is it genuine, or just a replication of what people actually want to see? How authentic are these images, and how staged are they? The image of a destination influences a lot the experience of the tourist. It creates expectations and develops certain stereotypes that many times create staged experiences. A destination image certainly involves staged characteristics; it implies a front and a back stage, which separate the processes shown to the consumer/ tourist, from the real processes happening behind. This simple segregation causes an enormous outcome on the consumer, who does not get to see the real face of the destination visited, and instead remains with a false and misleading image of the place. Portugal has become famous due to its outstanding landscapes and cultural resources, but mostly for its people and their welcoming character. Since we can remember, it has been a country known for its modesty and humbleness, and exactly this image would accompany it along the years, in order to guarantee its position in the tourism industry. These characteristics can be traced back to the regime of the dictator António de Oliveira Salazar, who helped to establish the image of the “humble” Portugal in the 20th century. Today we can find Portugal booming in terms of tourism; especially the capital Lisbon has noted a remarkable increase in the past time. In line with this, it has been elected the World´s Leading City Break Destination for the last three years. Thus, Lisbon has developed very rapidly; it is seen as a city of diversity and variety, authentic experiences and urban creations; its fast development and strong attraction have led to a strong influx of tourists, which is now breaking the records. Nevertheless, it can be noticed that globalization has taken over the capital and has already made some changes in terms of economy, culture and its social structure. But to what extent did this progress influence the authenticity and the genuineness of the real Lisbon and its people? Demonstrations The Influence of Destination Branding and Authenticity on Tourism: Analysing the tourist experience – Case Study of Lisbon vi and initiatives have marked the life within the city: locals protest against the current touristification and massification of the central areas and are no longer willing to bear the modification of their loved homes. At this point conflicts and barriers are built between the inhabitants, the official authorities, and the tourists. How exactly these conflicts influence the life of the locals, and how they affect the tourists experience in the city of Lisbon will be exposed and analysed in the present dissertation.

‘Destination Branding’: um conceito que guiou a indústria do turismo desde o primeiro dia. Um método, que reforça a posição do produto no mercado, e que ajuda a manter a competitividade na indústria. O ‘Destination Branding’ tem sido um instrumento eficiente para comunicar uma imagem concreta do destino e transmitir essa imagem ao consumidor final/turista. Quanto à realidade dos destinos, surge a pergunta: que ‘verdade’ transmite essa imagem? Essa imagem é genuína, ou apenas uma réplica das expetativas dos turistas? Quão autênticas são estas imagens, e quão encenadas são? Uma coisa, porém, é certa: a imagem de um destino influencia a experiência do turista. Essa imagem cria expetativas, e constrói certos estereótipos, que muitas vezes resultam em experiências, que não correspondem á realidade. É por esse motivo que a imagem do destino certamente implica e envolve algumas características ‘encenadas’. No entanto, esse procedimento implica os chamadas ‘front’ e ‘back stages’, que separam os processos apresentados aos consumidores/turistas dos verdadeiros processos que estão a acontecer por trás do cenário. Essa segregação causa um impacte significativo no consumidor, que acaba por não conhecer a verdadeira face do destino, e permanecer com uma imagem enganadora do local. Portugal tornou-se um destino turístico muito procurado, devido às suas paisagens excecionais e aos seus recursos culturais, mas, acima de tudo, graças à sua gente e ao seu carácter acolhedor. Devemos lembrar, que esse mesmo país foi sempre conhecido pela sua humildade e simplicidade; é exatamente essa imagem que tem acompanhado Portugal ao longo dos anos, de modo a garantir a sua posição no setor do turismo. Estas características acompanham a imagem turística deste país desde o regime do ditador António de Oliveira Salazar, que ajudou a construir e criar a imagem de um ‘Portugal modesto’ no século XX. Atualmente, em termos de turismo, Portugal está numa posição cimeira, sobretudo a capital, Lisboa, que registou um aumento notável nos últimos anos, no que toca à chegada de turistas. Lisboa foi também eleita a World´s Leading City Break Destination nos últimos três anos e tem-se desenvolvido muito rapidamente num passado recente; é uma The Influence of Destination Branding and Authenticity on Tourism: Analysing the tourist experience – Case Study of Lisbon viii cidade que representa a diversidade e a variedade, experiências autênticas e criações urbanas. Assim, o desenvolvimento acelerado conduziu a um enorme fluxo de turistas, que está a bater todos os recordes. Contudo, percebe-se que a globalização tem estado a apoderar-se da cidade, e tem até causado mudanças significativas em termos de economia, sociedade, e cultura dos locais. Mas até que ponto é que esse desenvolvimento influencia a autenticidade e a genuinidade de Lisboa e do seu povo? Manifestações e outras iniciativas marcaram os últimos anos da cidade: os habitantes protestam contra a forte turistificação e massificação de locais centrais, e não estão dispostos a aceitar a transformação das suas residências. Sucedem-se, então, conflitos entre os habitantes, as autoridades, e os turistas. O modo como esses conflitos influenciam a vida dos habitantes, e como isso afeta a experiência do turista na cidade de Lisboa, será exposto e analisado na presente dissertação.
Keywords: Authenticity; Destination images; Globalization; Lisbon; Tourist experience; Autenticidade; Globalização; Imagem do destino; Lisboa; Experiência do turista